2005
DOI: 10.4049/jimmunol.175.12.8415
|View full text |Cite
|
Sign up to set email alerts
|

Functional and Phenotypic Characterization of CD57+CD4+ T Cells and Their Association with HIV-1-Induced T Cell Dysfunction

Abstract: HIV-1 replication is associated with reduced or absent HIV-1-specific CD4+ T cell proliferation and skewing of HIV-1-specific CD4+ T cells toward an IFN-γ-producing, CCR7− phenotype. The CCR7− T cell population is heterogeneous and can be subdivided based on the expression of CD57. Although CD57 expression on CD8+ T cells is associated with proliferation incompetence and replicative senescence, less is known about the function of CD57-expressing CD4+ T cells. In this study, the frequency, phenotype, and functi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
124
3

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 133 publications
(135 citation statements)
references
References 43 publications
8
124
3
Order By: Relevance
“…We have previously shown that HIV-specific CD4 ϩ T cells are skewed by viral replication toward an effector memory T (T Em ) cell 3 phenotype as identified by the loss of CCR7 and the acquisition of CD57 (1,2). HIV-specific CD4 ϩ T Em cells from subjects with chronic HIV infection proliferate poorly and lack the ability to secrete IL-2 (2-4).…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously shown that HIV-specific CD4 ϩ T cells are skewed by viral replication toward an effector memory T (T Em ) cell 3 phenotype as identified by the loss of CCR7 and the acquisition of CD57 (1,2). HIV-specific CD4 ϩ T Em cells from subjects with chronic HIV infection proliferate poorly and lack the ability to secrete IL-2 (2-4).…”
Section: T Cell Dysfunction In Chronic Hiv Infection Is Closelymentioning
confidence: 99%
“…Biexponential scaling was used in all dot plots. We examined the expression of PD-1 only on cytokine-producing cells with frequencies Ն0.04% to ensure an adequate number of events for a valid analysis as previously validated by our laboratory (1,2).…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Biexponential scaling was used in all dot plots. Because the frequency of beryllium-specific CD4 ϩ T cells in blood tends to be low, we only examined the expression of PD-1 on cytokine-producing cells with frequencies Ն0.04% to ensure an adequate number of events for analysis as previously described (31)(32)(33). The CFSE-blocking experiments were acquired using a FACSCalibur flow cytometer (BD Immunocytometry Systems), and CellQuest Pro software was used to analyze the data.…”
Section: Flow Cytometrymentioning
confidence: 99%
“…Proliferation assays were performed using PBMCs and BAL cells (2 ϫ 10 6 cells/well) labeled with 2.0 M CFSE (Molecular Probes) (31,32). The CFSE-labeled cells were cultured at 37°C for 5 days in a humidified 5% CO 2 atmosphere in RPMI 1640 supplemented with 10% heat-inactivated human serum, 20 mM HEPES, 1 mM sodium pyruvate, 100 U/ml penicillin, 100 g/ml streptomycin, and 2 mM L-glutamine (all from Invitrogen Life Technologies) with the addition of either medium, 10 g/ml platebound anti-CD3, or 100 M BeSO 4 .…”
Section: Proliferation Assaymentioning
confidence: 99%
“…Significant increases in relative frequency of CD57 ϩ T cells have been reported in situations of persistent viral infection and chronic inflammation (41,42). Recently, CD57 expression on CD4 and CD8 lymphocytes was also associated with replicative senescence and terminal differentiation (31,32). It is commonly accepted that this is the result of chronic activation due to persistent Ag exposure.…”
Section: Discussionmentioning
confidence: 99%